IMPROVEMENT IN ADOLESCENTS' LISTENING SKILLS, SPEECH ARTICULATION, AND MUSICAL COLLABORATION THROUGH THE HARMONI MUSIC AND VOCAL TRAINING MODEL - Yoyok Febrijanto; Akde Triyoga; Amadea Farelliana; Valensia Serafin L.N (Suluh Adiluhung Publisher (SAPub), 2026)
This community service article reports the implementation and evaluation of the HARMONI music and vocal training model for adolescents at Gereja Baptis Indonesia (GBI) Sahabat Kediri. The program was designed to address the need for structured youth regeneration in church music ministry while strengthening listening skills and speech articulation through integrated musical learning. A one-group pre-test post-test design was used with 20 adolescents aged 13-17 years. The intervention consisted of participatory training in guitar, drum, keyboard, and vocal practice based on seven HARMONI stages: Hearing, Articulation, Rhythm, Music, Oral, Notation, and Integration. Data were collected using a 15-item questionnaire with a 1-4 scale, performance observation, and semi-structured interviews. The total score increased from a pre-test mean of 35.55 (SD = 2.42) to a post-test mean of 50.85 (SD = 1.90), with a mean gain of 15.30 points or 43.4%. Improvement was observed in all domains: listening skills (35.5%), speech/vocal articulation (39.7%), and musical skills, collaboration, and practice discipline (59.8%). Interview findings indicated that participants became more able to follow tempo, pronounce lyrics clearly, regulate breathing, understand simple song patterns, and participate more confidently in group performance. The findings suggest that HARMONI is a feasible community-based model for combining music skill development, auditory training, vocal articulation, and youth character formation. Continued mentoring, small-group practice, and peer support are recommended to sustain the program outcomes.